Metarhizium robertsii alters sugarcane volatiles and their interactions with insects - Pec Hernández, Marvin Mateo (2025)
Endophytic entomopathogenic fungi are a promising strategy for enhancing crop resistance to various biotic and environmental stresses. However, their effects on altering plant chemical defenses and shaping interactions with herbivores and natural enemies are still not fully understood. In this study, we investigated the potential of the endophytic entomopathogenic fungus Metarhizium robertsii to enhance sugarcane defenses in both the presence and absence of herbivores, focusing on two major crop pests, Diatraea saccharalis and Spodoptera frugiperda. First, we assessed the impact of M. robertsii inoculation on healthy plants and D. saccharalis-infested plants by measuring jasmonic acid (JA) and salicylic acid (SA) levels, diurnal volatile organic compound (VOC) emissions, the oviposition preference of D. saccharalis, and the olfactory attraction of the parasitoid Cotesia flavipes. Second, we evaluated the effects of M. robertsii on healthy and S. frugiperda-infested plants, focusing on changes in JA and SA levels, nocturnal VOC emissions, and the attraction of the predator Doru luteipes. Our results showed that M. robertsii inoculation alters JA and SA contents, as well as diurnal VOC emissions, enhancing both direct and indirect defenses in sugarcane. Specifically, inoculated plants without infestation showed reduced oviposition by D. saccharalis, while those with infestation attracted more parasitoids. However, the attraction effects varied by natural enemy, since the nocturnal predator showed no increased attraction to inoculated plants, regardless of infestation, even when nocturnal VOC emissions were altered. These findings suggest that M. robertsii has the potential to improve pest management by enhancing sugarcane defenses against D. saccharalis. However, they also highlight the complexity of interactions among M. robertsii, sugarcane, herbivores, and natural enemies, indicating that not all plant defense responses benefit each natural enemy equally.